2014
DOI: 10.1016/j.chroma.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acid-induced conformational variability on protein separation in reversed phase high performance liquid chromatography

Abstract: 26Influence of acid concentration in the mobile phase on protein separation was studied in a 27 wide concentration range of using trifluoroacetic acid (TFA) and formic acid (FA). At low,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…peaks increased in intensity with longer heating times. Bobály et al (2014), on the other hand, observed increased molar ellipticity values in CD spectra for lysozymes in acidic conditions, similar to what we observed in our systems at pH 3.5 and 6.5, heated to 75°C for 40 min (Fig. 3b).…”
Section: Circular Dichroismsupporting
confidence: 91%
“…peaks increased in intensity with longer heating times. Bobály et al (2014), on the other hand, observed increased molar ellipticity values in CD spectra for lysozymes in acidic conditions, similar to what we observed in our systems at pH 3.5 and 6.5, heated to 75°C for 40 min (Fig. 3b).…”
Section: Circular Dichroismsupporting
confidence: 91%
“…As shown in Fig. 6, a baseline separation of four proteins was achieved within only seven min using a 2 min gradient of ACN from 3.2 to 30% in mobile phase, which is superior to the separation performance of RP monolithic column poly (AOD-co-EDMA) for same protein standards [29] and some packed RP columns [39]. It was also noticed that the peak shapes of all four proteins are sharp, indicating that there is little nonspecific protein adsorption when using this novel IAM monolithic column.…”
Section: Application Of the Poly(mdpc-co-edma) Monolithmentioning
confidence: 92%
“…When liquid chromatography is online hyphenated to mass spectrometry, the advantages of using TFA for peptide separation quickly become significant disadvantages since the stable ion pairs and the increased surface tension of solutions with TFA prevent efficient ionization using electrospray. , Much effort has been spent on keeping TFA usable for LC-MS of peptides and proteins because of its superior chromatographic properties, particularly in RPLC of proteins, where it dramatically limits undesirable secondary interactions and maintain the compact structure of the analytes. While the superior chromatographic performance of TFA, or recently its less fluorinated alternative difluoroacetic acid, added to the mobile phase at least in some percentage, may still predominate the signal suppression in protein LC-MS analyses, , modern stationary phases with reduced silanol activity and positive surface charge enable efficient separation of peptides only with formic acid.…”
Section: Rplc Methods For Bottom-up Proteomic Analysesmentioning
confidence: 99%